THE IMPLEMENTATION OF GENRE BASED APPROACH IN TEACHING DISCUSSION TEXT - Ilham Ilham; Aminullah Aminullah (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2014)
The purposes of this study were to analyze the english teacher’s implementation of Genre Based Approach in teaching discussion text and to find out the difference between the students’ writing before and after implementation of Genre Based Approach. The study was a descriptive qualitative research design with characteristics of case study which focus on holistic description and explanation. This research was conducted in Fourth Semester Students of Muhammadiyah University of Mataram in academic year 2012/2013. The research was employed two data collection procedures particularly classroom observation and documentation of students text which was analyzed by using functional grammar. The results of this study shows that teacher applied Genre Based Approach in teaching discussiontext based on teaching and learning cycles such as Building Knowledge Of Field, Modelling Of Text, andIndependent Construction Of Text. This study also reveals that students can arrange discussion text regarding to schematic structure and language feature especially transitivity system. This study recommends that the Genre Based Approach should be implemented in teaching writing and The students in tertiary level should understand and mastery on schematic structure and language feature of text types regarding to functional grammar.